Decoding Demographics on Generation Z's Post-Pandemic Shopping Trends: E-Commerce Evolution 4.0, the Digital Shopper's Dilemma, and Tailoring Strategies - Islam, Khadija; Polas , Mohammad Rashed Hasan; Parvin, Kohinur; Akter, Tahmina (International Journal of Business, Management and Economics, 2023)
This quantitative study investigates the impact of demographic factors on customer satisfaction and subsequent online purchase intentions among Generation Z university students in Dhaka, Bangladesh, during the post-COVID-19 era. Employing a cross-sectional research design, the study uses a stratified random sampling technique to collect data from 433 respondents. The questionnaire, based on a five-point Likert scale, explores variables such as gender, internet literacy, product price perception, income, education, customer satisfaction, and intention to purchase. IBM SPSS Version 25 (Licensed) is used for data analysis, incorporating descriptive statistics, correlation analysis, and regression analysis. The study unveils positive and significant relationships between gender, internet literacy, product price, income, and education with customer satisfaction. Moreover, a robust link between customer satisfaction and the intention to purchase online is identified. Theoretical frameworks such as Social Identity Theory and Consumer Satisfaction Models guide the research, highlighting the importance of a nuanced understanding for tailored marketing strategies. The findings contribute valuable insights for businesses and policymakers navigating the post-COVID-19 digital landscape. Future research avenues include exploring emerging technologies and cross-cultural variations within Generation Z.